Frog nest foams exhibit pharmaceutical foam-like properties. Issue 9 (8th September 2021) - Brozio, Sarah; O'Shaughnessy, Erin M.; Woods, Stuart; Hall-Barrientos, Ivan; Martin, Patricia E.; Kennedy, Malcolm W.; Lamprou, Dimitrios A.; Hoskisson, Paul A.
Abstract : Foams have frequently been used as systems for the delivery of cosmetic and therapeutic molecules; however, there is high variability in the foamability and long-term stability of synthetic foams. The development of pharmaceutical foams that exhibit desirable foaming properties, delivering appropriate amounts of the active pharmaceutical ingredient (API) and that have excellent biocompatibility is of great interest. The production of stable foams is rare in the natural world; however, certain species of frogs have adopted foam production as a means of providing a protective environment for their eggs and larvae from predators and parasites, to prevent desiccation, to control gaseous exchange, to buffer temperature extremes, and to reduce UV damage. These foams show great stability (up to 10 days in tropical environments) and are highly biocompatible due to the sensitive nature of amphibian skin. This work demonstrates for the first time that nests of the túngara frog ( Engystomops pustulosus ) are stable ex situ with useful physiochemical and biocompatible properties and are capable of encapsulating a range of compounds, including antibiotics. These protein foam mixtures share some properties with pharmaceutical foams and may find utility in a range of pharmaceutical applications such as topical drug delivery systems.